Meningkatkan Pemahaman Konsep Nilai Tempat Melalui Media Blok Dienes bagi Anak Diskalkulia - Wiliati, Wenni; Zulmiyetri, Zulmiyetri (Jurnal Penelitian Pendidikan Khusus, 2021)
This research background by problems that have been found by researches at SD Negeri 02 Cupak Tangah, Padang city, a dyscalculia student who had problems in the concept of place value that is cannot distinguish unit numbers, tens and hundreds. The purpose of this research is to find out if the media of Dienes Block can improve the understanding of the concept of the value of the place of units, tens and hundreds for dyscalculia children. This study using of approach Single Subject Research (SSR) with A-B-A reseach design and graphic visual analysis techniques. Data collection techniques in this study were conducted with interviews, observations, documentation and tests by providing questions as many as 30 points for each session. The results of this study prove that dienes block media can improve the understanding of the concept of place value.